2016
DOI: 10.5424/fs/2016252-07317
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thinning intensity and canopy type on Scots pine stand and growth dynamics in a mixed managed forest

Abstract: Aim of the study: We analysed the effects of thinning intensity and canopy type on Scots pine growth and stand dynamics in a mixed Scots pine-beech forest.Area of the study: Western Pyrenees. Material and methods:Three thinning intensities were applied in 1999 (0, 20 and 30% basal area removed) and 2009 (0, 20 and 40%) on 9 plots. Within each plot, pure pine and mixed pine-beech patches are distinguished. All pine trees were inventoried in 1999, 2009 and 2014. The effects of treatments on the tree and stand st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
4
13
0
1
Order By: Relevance
“…Site conditions (poor vs. fertile sites) are important for biomass productivity of mixtures compared to monocultures (Pretzsch, Schütze 2014). A negative effect of beech on the pine growth was observed on unthinned plots by Primicia et al (2016) in the western Spanish Pyrenees. Konôpka et al (2016) found that the morphology of beech foliage is more plastic than that of spruce, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Site conditions (poor vs. fertile sites) are important for biomass productivity of mixtures compared to monocultures (Pretzsch, Schütze 2014). A negative effect of beech on the pine growth was observed on unthinned plots by Primicia et al (2016) in the western Spanish Pyrenees. Konôpka et al (2016) found that the morphology of beech foliage is more plastic than that of spruce, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Las densidades de regeneración de las plántulas en masas monoespecíficas se basaron en las tablas regionales de crecimiento y producción para estas especies (Madrigal et al 1992;Puertas 2003). González de Andrés et al (2017a) identificaron los valores iniciales de regeneración que mejor emulaban la composición de los rodales observada en inventarios realizados en 1999 y 2013-14 (Blanco 2004;Primicia et al 2016). Sobre estos valores (denominado regeneración típica), se realizó un análisis de sensibilidad, realizando una reducción y un aumento de la densidad inicial a diferentes intensidades: reducción moderada (-20%), reducción severa (-35%), aumento moderado (+20%) y aumento severo (+35%), generando un rango de densidades iniciales de 6175 a 12 825 árboles ha -1 , valores típicos para estas masas (Schwendtner 2012).…”
Section: Escenarios De Regeneraciónunclassified
“…As a matter of fact, in Scots pine heavy thinnings do not generate a surplus of growth compared to moderate ones, on the contrary [129]. Pine plantations from recovered sites can be managed, with moderate intensities, also after the age at which growth enters declining, depending on the state of tree health.…”
Section: Trees Response To Managementmentioning
confidence: 99%